2015
DOI: 10.2118/168001-pa
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Element Studies of Hoop-Stress Enhancement for Wellbore Strengthening

Abstract: In the drilling of deep horizons, the mud-weight window between pore-pressure gradient and fracture gradient often narrows because of rock properties and underground-stress state. Nonproductive-time events such as lost circulation, wellbore instability, kicks, underground crossflow, and pipe sticking are more likely. Such problems greatly increase drilling costs. Bridging pre-existing natural fractures or drilling-induced fractures with lost-circulation materials (LCM) is often performed to increase fracture g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(14 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The above analysis has shown that increased FIP and thus wellbore strengthening can be achieved by forming a mudcake on the wellbore wall. Another major method in the drilling industry to strengthen a wellbore is the technique based on bridging fractures on the wellbore wall (Alberty and McLean 2004;Feng et al 2015;Feng and Gray 2016a;Song and Rojas 2006). In this section, wellbore strengthening effects created by a mudcake and by the fracturebridging method are compared.…”
Section: Comparison With Fracture-bridging Wellbore Strengthening Methodsmentioning
confidence: 99%
“…The above analysis has shown that increased FIP and thus wellbore strengthening can be achieved by forming a mudcake on the wellbore wall. Another major method in the drilling industry to strengthen a wellbore is the technique based on bridging fractures on the wellbore wall (Alberty and McLean 2004;Feng et al 2015;Feng and Gray 2016a;Song and Rojas 2006). In this section, wellbore strengthening effects created by a mudcake and by the fracturebridging method are compared.…”
Section: Comparison With Fracture-bridging Wellbore Strengthening Methodsmentioning
confidence: 99%
“…Numerical methods have been used to model stresses, deformations and stabilities of boreholes caused by drilling (Feng et al 2015;Feng and Gray 2018;Zhang et al 2003Zhang et al , 2007. In this study, the FEM is used to model stresses and deformations of near-wellbore hydraulic fractures for wellbore strengthening applications.…”
Section: -D Fem Modeling Of Fracture Widthsmentioning
confidence: 99%
“…In recent years, the finite element method has been widely used in the study of rock breaking problems [4][5][6][7][8][9]. Jaime [10] employed the Lagrangian finite element method in modeling the rock cutting process.…”
Section: Finite Element Simulation Modelmentioning
confidence: 99%